Plasma oxidative stress is induced by single‐sprint anaerobic exercise in young cigarette smokers. (8th November 2012) - Taito, Shunsuke; Sekikawa, Kiyokazu; Oura, Keisuke; Kamikawa, Norimichi; Matsuki, Ryosuke; Kimura, Tatsushi; Takahashi, Makoto; Inamizu, Tsutomu; Hamada, Hironobu
Summary Cigarette smoking increases oxidative stress, which is a risk factor for several diseases. Smoking has also been reported to enhance plasma oxidative stress during strenuous exercise. However, no prior study has examined the changes in plasma oxidative stress after single‐sprint anaerobic exercise in cigarette smokers. The purpose of this study was to investigate these changes in young cigarette smokers by measuring reactive oxygen species generation and total antioxidant content. Participants were 15 male smokers (mean age: 25·9 ± 2·9 years) and 18 male non‐smokers (mean age: 24·2 ± 4·3 years). Hydroperoxide concentration and biological antioxidant potential (BAP) in plasma were measured at baseline and after the Wingate anaerobic test. A significant interaction between group and time was observed for plasma hydroperoxide concentration (P = 0·037). Plasma hydroperoxide concentration was significantly increased after exercise in both smokers and non‐smokers (P = 0·001 and <0·001, respectively). However, no significant interaction was observed between groups by time on plasma BAP (P = 0·574), and a main effect of time was observed (P<0·001). Plasma BAP was significantly increased after exercise in both groups (both, P<0·001). These findings indicate that plasma oxidative stress is higher in cigarette smokers than in non‐smokers after single‐sprint anaerobic exercise, which may increase the risk of oxidative damage.